Investigation of Interaction of CT-DNA with New Nickel and Palladium Complexes Containing Ferrocene Group with N and S Donor Atoms - Mohsen Atghaei; Bita Shafaatian; Seyyed Ahmad Rezvani (شیمی کاربردی روز)
New complexes of nickel(II) and palladium(II) were synthesized using the ferrocenyl imine ligand. This Schiff base ligand was coordinated to the metal ions through the imine N and thiolic S atoms. The synthesized complexes were characterized by FT-IR, 1H NMR, UV–Vis spectroscopy and elemental analysis. The IR spectra of complexes show characteristic of imine group. Furthermore, the 1H NMR spectra display different protons of the cyclopentadienyl groups. The binding interactions of the compounds with DNA were investigated by the electronic absorption spectroscopy, and the intrinsic binding constants (Kb) were calculated for the Schiff base ligand, nickel and palladium complexes as 2.7×104, 1.2×105 and 7.2×104, respectively. The obtained data showed that the synthesized compounds bind to DNA via intercalative binding modes. Also, viscosity was investigated in order to further explore the nature of interactions between the compounds and DNA. Accordingly, it was found that the synthesized compounds bind to DNA via intercalative binding modes.